Evaluation of Histomorphological Parameters to Predict Occult Nodal Metastasis in Early-Stage Oral Squamous Cell Carcinoma - Rahul VERMA; Ashok SINGH; Nilotpal CHOWDHURY; Prashant Pranesh JOSHI; Prashant DURGAPAL; Shalinee RAO; Sanjeev KISHORE (Federation of Turkish Pathology Societies, 2022)
Objective: The oral squamous cell carcinoma (OSCC) treatment protocol depends upon lymph node metastasis. Elective neck dissection for early-stage OSCC (pT1/T2) elective neck dissection reduces the morbidity rate. It also reduces the overall survival and thus it becomes important to detect lymph node metastasis in early-stage OSCC. Material and Method: Various histomorphological parameters have been studied to predict nodal metastasis in early-stage OSCC. We aim to evaluate these parameters in the context of nodal metastasis. 78 cases of early-stage OSCC were included in the study with histopathologic parameters like tumor size, grade, tumor depth of invasion (DOI), lymphovascular invasion (LVI), perineural invasion (PNI), worst pattern of invasion (WPOI), and lymph node level. Results: Out of the 78 patients, 32 patients had lymph node metastasis. T stage, DOI, LVI, and WPOI showed statistically significant deviance from the null model (P-values of 0.007, 0.01, 0.04 and 0.02 respectively). The Odds Ratio (OR) of T stage, DOI, LVI and WPOI were 4.45 (95% C.I =1.47-14.1), 4.4 (95% C.I =1.32-15.88), 8.12 (95% C.I =1.002-198.20), and 3.39 (95% C.I =1.24-9.74) respectively. On multivariate analysis (Firth logistic regression) using DOI, LVI, and WPOI as independent variables, only T-stage and WPOI retained statistical significance. Conclusion: The prognostic information supplied by evaluating DOI, LVI, and WPOI warrants the inclusion of these parameters in the standard reporting format for all cases of OSCC.